Hire right\fire right : a manager's guide to employment practices that avoid lawsuits - Roberson, Cliff (New York : McGraw-Hill, Inc., 1992)
Social Science
Includes index and bibliographical references
2000-08-09
Keywords: Personnel; Employment service; United Stetes